1999
DOI: 10.1111/0022-1082.00168
|View full text |Cite
|
Sign up to set email alerts
|

CEO Involvement in the Selection of New Board Members: An Empirical Analysis

Abstract: We study whether CEO involvement in the selection of new directors inf luences the nature of appointments to the board. When the CEO serves on the nominating committee or no nominating committee exists, firms appoint fewer independent outside directors and more gray outsiders with conf licts of interest. Stock price reactions to independent director appointments are significantly lower when the CEO is involved in director selection. Our evidence may illuminate a mechanism used by CEOs to reduce pressure from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
559
4
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,108 publications
(611 citation statements)
references
References 22 publications
45
559
4
3
Order By: Relevance
“…These results are consistent with the study made by Andrade, Salazar, Calegário and Silva (2009), who found an average of 10 members, with a pattern deviation of 5.46 for the year 2004, and to the study of Gondrige, Clemente and Espejo (2012), which found an average size of 11 members in Brazil. The results are also similar to those found by Shivdasani and Yermack (1999), who found an average size of 11 members for companies in the USA. However, these figures indicate that in Brazil the companies have relatively larger size of the Board of Directors as compared to an average of 6.6 found in New Zealand (Prevost, Rao, & Hossain, 2002); 6.8 in Chile (Lefort & Urzúa, 2008); and 7.13 in Colombia (Pombo & Gutiérrez, 2011).…”
Section: Dualitysupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with the study made by Andrade, Salazar, Calegário and Silva (2009), who found an average of 10 members, with a pattern deviation of 5.46 for the year 2004, and to the study of Gondrige, Clemente and Espejo (2012), which found an average size of 11 members in Brazil. The results are also similar to those found by Shivdasani and Yermack (1999), who found an average size of 11 members for companies in the USA. However, these figures indicate that in Brazil the companies have relatively larger size of the Board of Directors as compared to an average of 6.6 found in New Zealand (Prevost, Rao, & Hossain, 2002); 6.8 in Chile (Lefort & Urzúa, 2008); and 7.13 in Colombia (Pombo & Gutiérrez, 2011).…”
Section: Dualitysupporting
confidence: 90%
“…Besides, they generally have bigger Board of Directors, especially composed by great clients and local companies' leaders. This criterion was also adopted by Shivdasani and Yermack (1999). It is also justified since in Brazil these companies have different systems regarding accrual basis (Lopes & Tukamoto, 2007 The outliers effect was analyzed for the dependent variables Tobin's Q and ROE, through the interquartile range criterion (IQR), also used by Groβ (2007).…”
Section: Research Methodsologymentioning
confidence: 99%
“…According to the Agency theorists, CEO Duality creates imbalance in corporate power distribution as heavy concentration of management and control resides with one person which tend to jeopardised board effectiveness (Eisenhardt, 1989). This imbalance makes it inevitably difficult for the corporate board to provide appropriate monitoring or even institute punitive measure against erring CEO due to absence of independence (Jensen and Fama, 1983;Brickley et al, 1997;Keller et al, 2006;Dalton and Kesner, 1987;Shivdasani and Yermack, 1999;Goyal and Park, 2002;Wan and Ong, 2005;Morck et al, 1987;Dayton, 1984). The integrity of information available to board is compromised with CEO duality due to asymmetric as CEO determines what kinds of information are brought to board attention.…”
Section: Ceo Dualitymentioning
confidence: 99%
“…Supporting this argument, Shivdasani and Yermack (1999) provide evidence suggesting that when the CEO is involved in nomination process, the directors that are chosen are the ones, who are less likely to monitor effectively. The researchers show that in such a nomination process, a lower fraction of independent directors are selected and the likelihood of an independent board is lower.…”
Section: Wwwccsenetorg/ijefmentioning
confidence: 90%